(untitled) (Scientific journal of the Fergana State University, 2023)
The practical significance of the research results in this scientific research work is that the main methods used by highly qualified Greco-Roman wrestlers, the technical actions used in the competition and the individual characteristics of the wrestlers have been determined, and the results show the main methods that are often used during the competition. It is explained by the fact that it is possible to develop and standardize a set of technical methods for development and to introduce recommendations into the training process.